2018
DOI: 10.1088/1742-6596/1037/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

Noise emission from wind turbines in wake - Measurement and modeling

Abstract: Abstract. The influence of the wake of an upstream turbine impinging another one located further downstream is studied focusing on the latter's noise emission. Measurement data are investigated in the form of surface pressure fluctuations acquired using microphones flush-mounted in a wind turbine blade near its tip, characterizing the noise sources. Numerical results from a wind turbine noise model are also included in the analysis. The wind speed deficit and increased turbulence levels of the wake flow are cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The authors found good agreement between the measured and calculated results when background noise is neglected. The results of the proposed model correctly reproduce the quantitative increase in the ILFN as a function of wind speed; although, in some cases, differences with the measured data are apparent in some frequency ranges [32].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The authors found good agreement between the measured and calculated results when background noise is neglected. The results of the proposed model correctly reproduce the quantitative increase in the ILFN as a function of wind speed; although, in some cases, differences with the measured data are apparent in some frequency ranges [32].…”
Section: Introductionmentioning
confidence: 53%
“…The computational model proposed in [27] has been verified experimentally in papers [31,32]. The authors compared the results of the numerical calculations with the measured results for two test wind turbines located at the DTU-Riso station.…”
Section: Introductionmentioning
confidence: 99%